CFD Analysis to Study Effect of Circular Vortex Generator Placed in Inlet Section to Investigate Heat Transfer Aspects of Solar Air Heater - Vipin B. Gawande; A. S. Dhoble; D. B. Zodpe (The Scientific World Journal)
CFD analysis of 2-dimensional artificially roughened solar air heater duct with additional circular vortex generator, inserted in inlet section is carried out. Circular transverse ribs on the absorber plate are placed as usual. The analysis is done to investigate the effect of inserting additional vortex generator on the heat transfer and flow friction characteristics inside the solar air heater duct. This investigation covers relative roughness pitch in the range of 10 ≤ P/e ≤ 25 and relevant Reynolds numbers in the range of 3800 ≤ Re ≤ 18000. Relative roughness height (e/D) is kept constant as 0.03 for analysis. The turbulence created due to additional circular vortex generator increases the heat transfer rate and at the same time there is also increase in friction factor values. For combined arrangement of ribs and vortex generator, maximum Nusselt number is found to be 2.05 times that of the smooth duct. The enhancement in Nusselt number with ribs and additional vortex generator is found to be 1.06 times that of duct using ribs alone. The maximum increase in friction factor with ribs and circular vortex generator is found to be 2.91 times that of the smooth duct. Friction factor in a combined arrangement is 1.114 times that in a duct with ribs alone on the absorber plate. The augmentation in Thermal Enhancement Factor (TEF) with vortex generator in inlet section is found to be 1.06 times more than with circular ribs alone on the absorber plate.